COMPARATIVE DOSIMETRIC STUDY IN CHEST COMPUTED TOMOGRAPHY USING PHANTOMS (Brazilian Journal of Radiation Sciences, 2019)
The dissemination of Computed Tomography (CT) scan has promoted a significant increase in the absorbed dose by patients due to the diagnosis. Therefore, it is indispensable to improve protocols, seeking smaller doses, without impairing the diagnostic quality of the image. The risks of stochastic effects are greater for children due to tissue radiosensitivity coupled with longer life expectancy. In this work, a cylindrical phantom made of polymethylmethacrylate was used representing an adult chest, and a second phantom made of the same material was designed in an oblong shape, including axillary region, based on the dimensions of an eight year old pediatric patient. A comparative study was performed between chest scans formulated in two CT scanners in different radiodiagnostic services. The central slice of the both phantoms was irradiated successively, using a pencil ionization chamber, for the measurements in five different points of each phantom. From the measurements, we obtain values of weighted and volumetric Dose Index (CK,PMMA,vol). The scans were performed with the routine chest acquisition protocols of the radiodiagnostic services, both for a voltage of 120 kV X-ray tube supply voltage. This work allowed compare the absorbed dose between patients with variable chest volumes and the dose variation in patients between two equipments used for image generation with the same diagnostic objective.